The role of affective interference and mnemonic load in the dynamic adjustment in working memory. - Banks, Jonathan B.; Mallick, Anum; Nieto, Alexandra C.; Zanesco, Anthony P.; Jha, Amishi P. (Memory & Cognition, 2023)
The amount of cognitive control required during a task may fluctuate over the course of performing a task. The dynamic upregulation of cognitive control has been proposed to occur in response to conflict or in response to the need for additional control during demanding cognitive tasks. Specifically, upregulation in cognitive control results in improved performance on trials that follow more demanding trials. Recent work has demonstrated that upregulation occurs during following trials with high (vs. low) mnemonic load and negative (vs. neutral) affective interference during working memory tasks. Although dynamic upregulation appears to be a robust phenomenon, less is known about individual difference factors that may alter the likelihood to engage in upregulation as a result of a signal to increase cognitive control. The current study attempted to replicate prior findings that suggest upregulation may occur following higher load trials or affective interference during a working memory task. Further, the study examined anxiety, depressive symptomatology, working memory capacity, mood, and dispositional mindfulness and possible moderators for upregulation of cognitive control. Participants (N = 150) completed a delayed recognition working memory task with mnemonic load (High vs. Low) and affective interference (Negative vs. Neutral) parametrically manipulated. Participants completed measures of the individual difference factors. The current findings replicate prior work demonstrating an upregulation of cognitive control following high load trials and negative affective interference. Individual difference factors did not moderate the upregulation findings, suggesting that upregulation is a robust phenomenon that can be triggered by both affective interference and mnemonic load.